Analysis of Factors Affecting the Intention to Buy Halal Cosmetics - Fitriani Tobing; Raja Fajrillah; Amanda; Melany (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
The halal lifestyle trend is rapidly growing around the world. With the increasing number of Muslims population, the demand for halal products is also increasing. This study aiming to analyze the factors that influence consumer purchase intention towards halal cosmetic products. The factors used are product knowledge, religiosity, and Islamic advertising ethics. This research was conducted at the State Islamic University of North Sumatra by distributing questionnaires to 90 students. The data were processed using descriptive analysis and Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The research results show that product knowledge, religiosity, and Islamic advertising ethics have a significant positive influence on the intention to purchase halal cosmetics. A person's knowledge of a product is accompanied by their adherence to religion, US well US cosmetics advertising which applies the ethical values of Islamic advertising which causes an increase in purchase intention. This research provides a more comprehensive understanding of consumer behavior related to halal products. The The results of this study are also useful for stakeholders of the halal cosmetics industry and researchers interested in this field. Future research can explore other factors that influence Muslim consumers' purchase intention towards halal cosmetics.